Volume 7: Turbomachinery, Parts A, B, and C 2011
DOI: 10.1115/gt2011-45457
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Turbine Tip Leakage Flows on Exhaust Diffuser Performance

Abstract: This paper describes numerical simulation of the effect of turbine exhaust flows on typical exhaust diffuser geometries. The study has been carried out on three different diffuser geometries. These diffusers have varying degrees of diffusion in the annular section. The studies were carried out at a Reynolds number of 7.7 × 105 based on the diffuser inlet hydraulic diameter. The performance of the diffusers was assessed in terms of total pressure loss and static pressure coefficient across the diffuser. The tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The scope of this paper comprises the total pressure losses produced in the shroud boundary layer of the annular diffuser downstream of the rotor. Babu et al (2011) were able to demonstrate that rotor tip leakage, achieved by means of flow injection in the shroud region, allow to decrease total pressure loss in comparison to an idealised uniform inflow. In the investigation presented here, the tip jet is achieved by a rotor instead.…”
Section: Total Pressure Loss Coefficientmentioning
confidence: 97%
“…The scope of this paper comprises the total pressure losses produced in the shroud boundary layer of the annular diffuser downstream of the rotor. Babu et al (2011) were able to demonstrate that rotor tip leakage, achieved by means of flow injection in the shroud region, allow to decrease total pressure loss in comparison to an idealised uniform inflow. In the investigation presented here, the tip jet is achieved by a rotor instead.…”
Section: Total Pressure Loss Coefficientmentioning
confidence: 97%
“…For the effects of turbine tip leakage flows on the exhaust diffuser performance, Babu et al 16 found that the turbine exit flow was simulated by combining an injection scheme from the casing into the main flow that changes the uniform diffuser inlet velocity profile to that of a typical turbine exit flow profile. It was observed that typical axial turbine exit flows carry a thin tip-induced casing boundary layer (tipstrong flow), which energizes and enables the casing endwall flows to overcome adverse pressure gradients, and the current study also reinforces the fact that the volute diffuser performance is highly sensitive to inlet conditions.…”
Section: Effect Of Turbine Exit Conditions Simulated On the Nonaxisymmetric Exhaust Volutementioning
confidence: 99%
“…Great efforts have been made for understanding the effect of the turbine outlet flow field on diffuser performance, particularly that of tip jets induced upstream of the diffuser. Numerous authors, such as Babu et al (2011) and Volkmer et al (2011) found an increase in diffuser pressure recovery for increasing jet intensity. Mimic et al (2017) were able to correlate the diffuser pressure recovery with stage parameters of the blading, demonstrating a direct correlation between the intensity of tipgap vortices and boundary layer stabilization for an engine-like test rig.…”
Section: Introductionmentioning
confidence: 95%